Microbiomes of urban trees: unveiling contributions to atmospheric pollution mitigation - Gandolfi, Isabella; Canedoli, Claudia; Rosatelli, Asia; Covino, Stefano; Cappelletti, David; Sebastiani, Bartolomeo; Tatangelo, Valeria; Corengia, Davide; Pittino, Francesca; Padoa-Schioppa, Emilio; Báez-Matus, Ximena; Hernández, Lisette; et al. (Frontiers in Microbiology, 2024)
Urban trees are crucial in delivering essential ecosystem services, including air pollution mitigation. This service is influenced by plant associated microbiomes, which can degrade hydrocarbons, support tree health, and influence ecological processes. Yet, our understanding of tree microbiomes remains limited, thus affecting our ability to assess and quantify the ecosystem services provided by trees as complex systems. The main hypothesis of this work was that tree microbiomes concur to hydrocarbon biodegradation, and was tested through three case studies, which collectively investigated two tree micro-habitats (phyllosphere and tree cavity organic soil -TCOS) under various conditions representing diverse ecological scenarios, by applying different culture-based and molecular techniques and at different scales. The integration of all results provided a more comprehensive understanding of the role of microbiomes in urban trees. Firstly, bacterial strains isolated from the phyllosphere of Quercus ilex were characterized, indicating the presence of Plant-Growth Promoting bacteria and strains able to catabolize PAHs, particularly naphthalene and phenanthrene. Secondly, naphthalene biodegradation on artificially spiked Hedera helix leaves was quantified in greenhouse experiments on inoculated and untreated plants. The persistence of the inoculated strain and community structure of epiphytic bacteria were assessed by Illumina sequencing of V5-V6 hypervariable regions of 16S rRNA gene. Results showed that naphthalene degradation was initially faster on inoculated plants but later the degradation rates became similar, probably because bacterial populations with hydrocarbon-degrading abilities gradually developed also on non-inoculated plants. Finally, we explored bacterial and fungal biodiversity hosted by TCOS samples, collected from six large trees located in an urban park and belonging to different species. Microbial communities were characterized by Illumina sequencing of V5-V6 hypervariable regions of bacterial gene 16S rRNA and of fungal ITS1. Results indicated TCOS as a distinct substrate, whose microbiome is determined both by the host tree and by canopy environmental conditions and has a pronounced aerobic hydrocarbon degradation potential. Overall, a better assessment of biodiversity associated with trees and the subsequent provision of ecosystem services constitutes a first step toward developing future new microbe-driven sustainable solutions, especially in terms of support for urban green planning and management policy.